Anticancer Potential of Azatetracyclic Derivatives: In Vitro Screening and Selective Cytotoxicity of Azide and Monobrominated Compounds - Costel Moldoveanu; Ionel I. Mangalagiu; Gheorghita Zbancioc; Ramona Danac; Gabriela Tataringa; Ana Maria Zbancioc (Molecules)
This study investigated the antiproliferative activity of three classes of benzo[f]pyrrolo[1,2-a]quinoline azatetracyclic derivatives. All compounds were screened against 60 cancer cell lines at a single dose of 10 μM. When we compared the activity of the three classes of azatetracyclic derivatives (azide, monobrominated and dibrominated), we found that the dibrominated compounds were less active, while the azides were the most active molecules. Compounds 3b and 5a, showing the best growth inhibition profile of all the drugs evaluated, were selected for the second stage of a full five-dose testing. According to the results of the in vitro screening, compounds 3b and 5a exhibit good to moderate anticancer activity (in micromolar range) against all nine cancer sub-panels, with compound 5a being more selective than compound 3b. Both compounds presented better activity than phenstatin on T–47D breast cancer cells, with compound 3b also being more active on SK–MEL–28 melanoma cells, while compound 5a was more active than phenstatin on COLO 205 colon cancer cells. As for the probable mechanism of action, the benzoquinoline derivatives could act as PI5P4Kα and PI5P4Kβ inhibitors or topoisomerase II inhibitors.